Cyber attacks: Cross-country interdependence and enforcement - QIU-HONG WANG (Institutional Knowledge at Singapore Management University, 2009)
This study empirically characterizes the interdependence in cyber attacks and examines theimpact from the first international treaty against cybercrimes (Convention on Cybercrimes:Europe Treaty Series No. 185). With the data covering 62 countries over the period from year2003 to 2007, we find that, international cooperation in enforcement as measured by theindicator of joining the Convention on Cybercrimes, deterred cyber attacks originating from anyparticular country by 15.81% ~ 24.77% (in 95% confidence interval). Second, joining theConvention also affected the interdependence in cyber attacks from two angels. First, for anypair of country, closer status in joining or not joining the Convention was associated with lessnegative or more positive correlation. Second, joining the Convention or joining it earlier wasassociated with lower correlation between countries over time. We discuss the policyimplications from our findings to public authorities, cyber insurance companies andorganizational users.